Bioengineered material, method of preparation and use

CN122937286APending Publication Date: 2026-10-20SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510463093.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,这类材料难以进行个体化治疗,无法完全匹配角膜囊袋内部形状,而且材料嵌入后角膜厚度往往不稳定导致视力不稳定

Benefits of technology

[0033]第四方面,本申请实施例提供一种角膜的塑形方法,在角膜的内部生成目标空腔;将如上第一方面中任一所述的生物工程材料通过所述角膜上预设的切口注射进所述目标空腔;以及对所述目标空腔内的所述生物工程材料进行光照射,使得所述生物工程材料固化,从而增加所述角膜的厚度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005357812980000121
    Figure BDA0005357812980000121
  • Figure BDA0005357812980000122
    Figure BDA0005357812980000122
  • Figure BDA0005357812980000131
    Figure BDA0005357812980000131
Patent Text Reader

Abstract

This application provides a bioengineered material for reshaping the shape of biological tissue. The bioengineered material includes a target aqueous solution and a photoinitiator, wherein the photoinitiator can solidify the target aqueous solution under preset light conditions to generate a transparent target, thereby adapting to and supporting the biological tissue to be treated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of bioengineering materials, and more particularly to a bioengineering material, its preparation method, and its uses. Background Technology

[0002] Keratoconus is an eye disease characterized by the expansion and thinning of the central or paracentral cornea, which then protrudes forward in a cone shape. The cornea plays a crucial role in ocular refractive error. A normal human cornea is 500-550 μm thick, but in keratoconus, it is often thinner and irregularly shaped, leading to high irregular astigmatism, significant vision loss in later stages, and even blindness. The global incidence of keratoconus is 0.05-0.23%, and according to incomplete statistics, there are approximately one million people with keratoconus in China. This disease typically develops during adolescence and is a significant cause of blindness in my country, severely impacting patients' daily lives and work. Timely treatment is crucial for improving vision, alleviating symptoms, and preventing the condition from worsening.

[0003] There are various treatment options for keratoconus, such as scleral contact lenses, corneal collagen cross-linking, corneal stromal ring implantation, corneal stromal lenticule implantation, corneal transplantation, and artificial cornea implantation. Among the treatment options for keratoconus, the only one that can restore corneal thickness is corneal transplantation, which includes two types: penetrating keratoplasty and deep lamellar keratoplasty. Penetrating keratoplasty requires the removal of the entire diseased cornea and its replacement with a donor cornea; deep lamellar keratoplasty only replaces the anterior layer of the cornea, preserving the patient's own Descemet's membrane and endothelial cells. However, corneal transplantation has several drawbacks and potential risks. The transplanted donor cornea may be recognized as a foreign body by the patient's immune system, triggering a rejection reaction, leading to corneal opacity or loss of function, requiring long-term use of immunosuppressants. Secondly, the surgical incision is large, and postoperative bacterial, fungal, or viral infections may occur, which in severe cases may even affect the surgical outcome or cause further vision loss. Furthermore, corneal transplantation surgery is expensive, and postoperative care, medication costs, and potential subsequent treatments can all increase financial burden.

[0004] Currently, other conventional treatments for keratoconus cannot resolve the issue of corneal thinning. Corneal collagen cross-linking is the primary method to slow down corneal thinning. This method uses riboflavin as a photosensitizer under specific wavelengths of ultraviolet light to induce a cross-linking reaction in corneal collagen fibers, strengthening the corneal stroma and enhancing its biomechanical properties, thereby slowing down corneal thinning and deformation. However, it cannot restore corneal thickness or improve its shape. Furthermore, corneal stromal ring implantation involves a minimally invasive procedure to implant an arc-shaped material within the corneal stroma to reshape the cornea and correct its refractive power. However, this procedure only alters the corneal shape, does not change the central corneal thickness, and cannot prevent further corneal thinning.

[0005] In recent years, numerous clinical studies have been conducted on the treatment of keratoconus using corneal stromal lenticules. This method reshapes the cornea by implanting a lenticule into the corneal stroma. However, since the lenticule originates from a donor cornea, its effectiveness is heavily limited by the quality and shape of the donor cornea, leading to challenges such as surgical difficulty, limited visual improvement, uncertain long-term results, and postoperative complications. Due to these limitations, international research is developing artificial corneal implantation techniques for keratoconus. These techniques utilize fixed-shape artificial corneal scaffold materials embedded within the corneal stromal capsule to restore corneal thickness. However, these materials are difficult to personalize, cannot perfectly match the internal shape of the corneal capsule, and often result in unstable corneal thickness after implantation, leading to visual instability. Therefore, the treatment of keratoconus urgently requires a bioengineered material that can perfectly adapt to and restore the shape and thickness of the cornea to address these issues. In the current biomedical field, the demand for bioengineered materials capable of reshaping biological tissues is increasing, and research on keratoconus tissue reshaping materials also has significant potential applications in other fields such as dermal fillers and plastic surgery. Summary of the Invention

[0006] This application provides a bioengineering material, a preparation method, and its uses. The bioengineering material can be injected into biological tissue, and is in a liquid state before injection. After injection, it is transformed into a solid state through photocuring, thereby perfectly fitting and supporting the biological tissue to be treated.

[0007] To achieve the above objectives, the embodiments of this application adopt the following technical solutions:

[0008] In a first aspect, embodiments of this application provide a bioengineering material for reshaping the shape of biological tissues, comprising: a target aqueous solution, including a target polymeric material dissolved in a water-based solvent; and a photoinitiator solution configured to solidify the target aqueous solution under preset light conditions to generate a transparent target object.

[0009] According to some embodiments of this application, the photoinitiator solution includes a first photoinitiator configured to cause cross-linking within the target polymer material under preset illumination conditions; and a second photoinitiator configured to cause cross-linking of the target polymer material at the target interface with the biological tissue when the bioengineered material comes into contact with the biological tissue at the target interface under the preset illumination conditions.

[0010] According to some embodiments of this application, the second photoinitiator also causes the biological tissue in the target region adjacent to the target interface to crosslink.

[0011] According to some embodiments of this application, the first photoinitiator includes at least one of ketone photoinitiators, phosphonooxy photoinitiators, germane photoinitiators, azo photoinitiators, carbazole photoinitiators, xanthan photoinitiators, or bis(benzylidene)cycloalkanone two-photon initiators.

[0012] According to some embodiments of this application, the ketone photoinitiator includes at least one of camphorquinone, 1-hydroxycyclohexylphenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylacetone-1, or 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propanone; the phosphonophosphonoinitiator includes monoacylphosphono, diacylphosphono, phenyl(2,4,6-trimethylbenzoyl)phosphonite salt, or di(2,4,6-trimethylbenzoyl)phosphonite salt. The photoinitiator comprises at least one of the following: phosphonates; the germane photoinitiator comprises 1,6-bis[4-(trimethylgermanylcarbonyl)phenoxy]hexane; the azo photoinitiator comprises at least one of azobisisobutyrazoline hydrochloride, 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide] or azobisisobutyranidine hydrochloride; the carbazole photoinitiator comprises 1-(6-o-methylbenzoyl-N-ethylcarbazole)-1-ethyl ketone oxime ethyl ester; the xanthones photoinitiator comprises eosin Y; and the bis(benzylidene)cycloalkanone two-photon initiator comprises bis(2,4,6-trimethylbenzoyl)phenylphosphonate.

[0013] According to some embodiments of this application, the bioengineered material further includes at least one co-initiator configured to cooperate with the first photoinitiator to achieve internal crosslinking of the target polymer material.

[0014] According to some embodiments of this application, the co-initiator includes at least one of triethylamine, triethanolamine, N-methyldiethanolamine, arginine, or ethyl 4-dimethylaminobenzoate.

[0015] According to some embodiments of this application, the second photoinitiator includes at least an isorhozine cyclic photoinitiator; and the isorhozine cyclic photoinitiator includes at least one of riboflavin, flavin adenine dinucleotide, phosphorylated riboflavin, and sulfonated riboflavin.

[0016] According to some embodiments of this application, the bioengineered material has a transmittance of more than 80% at a light wavelength of 550 nm.

[0017] According to some embodiments of this application, the target aqueous solution is thermosensitive; and the bioengineered material remains in a semi-solid state within the target temperature range.

[0018] According to some embodiments of this application, the sol-gel transition temperature of the target aqueous solution is between 25°C and 40°C; the target aqueous solution is mixed with the photoinitiator solution to form a mixed solution.

[0019] According to some embodiments of this application, the biological tissue is a human cornea, and the mixed solution is injectable at a first temperature; at a second temperature, the mixed solution remains in a semi-solid state after being injected into a cavity within the cornea.

[0020] According to some embodiments of this application, the target polymeric material includes a thermosensitive material, which includes at least one of gelatin, gelatin derivatives, chitosan, chitosan derivatives, agar, agar derivatives, poly(N-isopropylacrylamide), poly(N-vinylcaprolactam), poly(N-vinylcaprolactam) derivatives, poly(N-vinylcaprolactam) triblock copolymer, or poly(D,L-lactic acid)-poly(ethylene glycol)-poly(D,L-lactic acid) triblock copolymer.

[0021] According to some embodiments of this application, the target polymer material contains functional groups capable of participating in photocrosslinking. The functional groups capable of participating in photocrosslinking include at least one selected from the following groups: double-bonded functional groups, alkynyl, mercapto, aldehyde, amino, or phenolic groups. The double-bonded functional groups include at least one selected from the following groups: vinyl, acryloyl, methacryl, acrylate, methacrylate, acrylamide, methacrylamide, norbornene, cinnamate, maleimide, fumarate, or vinyl ether.

[0022] According to some embodiments of this application, the target polymeric material includes a non-thermosensitive material, which includes at least one of hyaluronic acid, hyaluronic acid derivatives, silk fibroin, silk fibroin derivatives, collagen, collagen derivatives, alginic acid, alginic acid derivatives, dextran, dextran derivatives, polyethylene glycol, polyethylene glycol derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polylactic acid, polylactic acid derivatives, polyamino acids, polyamino acid derivatives, polypeptides, or polypeptide derivatives.

[0023] The target polymer material contains functional groups capable of participating in photocrosslinking. These functional groups include at least one of the following: double-bonded functional groups, alkynyl, mercapto, aldehyde, amino, or phenolic groups. The double-bonded functional groups include at least one of the following: vinyl, acryloyl, methacryl, acrylate, methacrylate, acrylamide, methacrylamide, norbornene, cinnamate, maleimide, fumarate, or vinyl ether.

[0024] According to some embodiments of this application, the water-based solvent further includes a buffer solution, which includes at least one of acetate buffer, carbonate buffer, amino acid buffer, phosphate buffer, citrate buffer, barbiturate buffer, Earl balanced salt buffer, Hanks balanced salt buffer, cell culture medium buffer, tris(hydroxymethyl)aminomethane buffer, or 4-hydroxyethylpiperazine ethanesulfonic acid buffer.

[0025] Secondly, embodiments of this application provide a method for preparing a bioengineering material, comprising obtaining a target aqueous solution and a photoinitiator solution as described in any of the first aspects above, wherein the target aqueous solution comprises a polymeric material dissolved in a water-based solvent, and the photoinitiator solution comprises a first photoinitiator or a mixture of a first photoinitiator and a second photoinitiator; and mixing the target aqueous solution and the photoinitiator solution according to a preset mass ratio to obtain a mixed solution.

[0026] According to some embodiments of this application, when the bioengineered material is used for corneal reshaping, the method further includes maintaining the mixed solution at a first temperature and injecting it into a preset storage space in the cornea through the injection opening of the cornea; and then adjusting the temperature to a second temperature, wherein the polymer material remains in a solution state at the first temperature and is injectable; and the polymer material remains in a semi-solid state at the second temperature.

[0027] According to some embodiments of this application, the mixed solution is subjected to a preset light irradiation treatment to obtain a solid bioengineering material.

[0028] According to some embodiments of this application, in the preset illumination process, the wavelength range of the irradiated light is 300nm to 900nm.

[0029] According to some embodiments of this application, the illumination time ranges from 1 second to 120 minutes during the illumination process.

[0030] According to some embodiments of this application, the target aqueous solution and the photoinitiator are mixed at a mass ratio of 99:1 to 1:1; the mass fraction of the target polymer material in the target aqueous solution is 0.1%-80%; and the mass fraction of the photoinitiator in the photoinitiator solution is 0.0001%-20%.

[0031] Thirdly, embodiments of this application provide a use of a bioengineering material, wherein the bioengineering material as described in any of the first aspects is used to fill the interior of the corneal tissue, thereby increasing the thickness of the cornea.

[0032] According to some embodiments of this application, the bioengineered material is used as a drug delivery system to provide targeted treatment to the cornea by filling the corneal tissue.

[0033] Fourthly, embodiments of this application provide a method for shaping the cornea, which involves generating a target cavity inside the cornea; injecting a bioengineering material as described in any of the first aspects above into the target cavity through a pre-set incision on the cornea; and irradiating the bioengineering material within the target cavity with light to solidify the bioengineering material, thereby increasing the thickness of the cornea. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of this specification, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this specification. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0035] Figure 1 A schematic diagram illustrating an application scenario of a bioengineering material provided according to embodiments of this specification is shown.

[0036] Figure 2 The compressive modulus of the hydrogel sample provided according to the embodiments of this specification is shown.

[0037] Figure 3 A test diagram of the support properties of a hydrogel sample provided according to an embodiment of this specification is shown.

[0038] Figure 4 A swelling test diagram of a hydrogel sample provided according to an embodiment of this specification is shown.

[0039] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown.

[0040] Figure 6 A graph showing the temperature-sensitive properties of a hydrogel sample provided according to an embodiment of this specification is shown.

[0041] Figure 7 A sol-gel transition diagram of a hydrogel sample provided according to an embodiment of this specification is shown.

[0042] Figure 8 A viscosity bar chart of a polymer mixture solution provided according to an embodiment of this specification is shown.

[0043] Figure 9 Viscosity histograms of the mixed solutions provided according to the embodiments of this specification under different temperatures and shear rates are shown.

[0044] Figure 10A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown.

[0045] Figure 11 A cytotoxicity graph of a hydrogel sample provided according to an embodiment of this specification is shown.

[0046] Figure 12 A surgical procedure flowchart according to an embodiment of this specification is shown.

[0047] Figure 13 A schematic diagram of a healthy cornea provided according to an embodiment of this specification is shown.

[0048] Figure 14 A schematic diagram illustrating the thickness variation of a hydrogel sample filling a healthy cornea according to embodiments of this specification is shown.

[0049] Figure 15 A schematic diagram illustrating the thickness variation of a hydrogel sample filling a healthy cornea according to embodiments of this specification is shown.

[0050] Figure 16 A bar graph showing the thickness of a hydrogel sample filling a healthy cornea according to embodiments of this specification is presented.

[0051] Figure 17 A bar chart showing the thickness maintenance of a hydrogel sample filling a healthy cornea according to embodiments of this specification is presented.

[0052] Figure 18 A schematic diagram of endothelial cells after a hydrogel sample provided according to an embodiment of this specification has been filled into the cornea.

[0053] Figure 19 A cross-sectional view of a molding die provided according to an embodiment of this specification is shown.

[0054] Figure 20 This illustration shows a cornea shaped by filling a healthy cornea with a hydrogel sample using a mold, as shown in this embodiment.

[0055] Figure 21 A schematic diagram of endothelial cells after a hydrogel sample provided according to an embodiment of this specification has been filled into the cornea.

[0056] Figure 22 Histological staining of the cornea after being shaped by a hydrogel sample, according to an embodiment provided in this specification, is shown. Detailed Implementation

[0057] The following description provides specific application scenarios and requirements for this specification, intended to enable those skilled in the art to make and use the contents of this specification. Various partial modifications to the disclosed embodiments will be apparent to those skilled in the art, and the general principles defined herein can be applied to other embodiments and applications without departing from the spirit and scope of this specification. Therefore, this specification is not limited to the embodiments shown, but rather to the widest scope consistent with the claims.

[0058] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not restrictive. For example, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” used herein may also include the plural forms. When used in this specification, the terms “comprising,” “including,” and / or “containing” mean that the associated integers, steps, operations, elements, and / or components are present, but do not exclude the presence of one or more other features, integers, steps, operations, elements, components, and / or groups, or that other features, integers, steps, operations, elements, components, and / or groups may be added to the system / method.

[0059] In this application, "X includes at least one of A, B, or C" means that X includes at least A, or X includes at least B, or X includes at least C. That is, X can include any combination of A, B, and C, or any combination of A, B, and C, as well as other possible content / elements. The arbitrary combination of A, B, and C can be A, B, C, AB, AC, BC, or ABC.

[0060] Considering the following description, these and other features of this specification, as well as the operation and function of related structural elements, and the economy of component assembly and manufacture, can be significantly improved. This description also includes all figures and text in the accompanying drawings, all of which form part of this specification. However, it should be clearly understood that the drawings are for illustrative and descriptive purposes only and are not intended to limit the scope of this specification. It should also be understood that the drawings are not drawn to scale.

[0061] In the current biomedical field, the demand for bioengineered materials capable of reshaping biological tissues is increasing. In the treatment of keratoconus, current techniques typically require transforming bioengineered materials into implants conforming to the shape and thickness of the tissue to be treated outside the body, and then implanting these implants into the tissue. For example, keratoconus can be treated using corneal stromal ring implantation. Specifically, medical professionals need to pre-customize an artificially synthesized corneal stromal ring based on the patient's specific ocular parameters outside the body. This artificially synthesized corneal stromal ring is then implanted into the cornea. While this method is an effective treatment for keratoconus, it has drawbacks. First, due to the complexity of corneal tissue and individual differences, it is often difficult to achieve a perfect match with the artificially synthesized corneal stromal ring, leading to poor postoperative adaptation. Second, this method only changes the shape of the cornea and cannot prevent the continued thinning of the cornea. Furthermore, this technique may lead to poor integration between the biomaterial and surrounding tissues, causing inflammation or other complications, affecting treatment effectiveness and the patient's overall recovery.

[0062] In view of this, this specification provides a bioengineering material, a preparation method, and its uses. The bioengineering material includes a target aqueous solution and a photoinitiator solution. The target aqueous solution and the photoinitiator solution are mixed to form a mixed solution. Under preset light irradiation conditions, the mixed solution can solidify into a transparent bioengineering material. Because this bioengineering material is in a liquid state before injection and solidifies under light irradiation after injection, it can perfectly adapt to surrounding tissues. Furthermore, because the above-mentioned bioengineering material has a certain thickness and becomes solid after solidification, it can increase the thickness and mechanical strength of biological tissues, thereby filling biological tissues and restoring them to their normal morphology.

[0063] Before describing the specific embodiments in this specification, the uses of the bioengineering materials provided in this specification will be introduced first.

[0064] The bioengineered materials provided in this specification can be used for filling the corneal tissue, thereby enhancing corneal thickness and mechanical strength. The application of these bioengineered materials to fill the corneal stroma is not limited to patients; they can also be used in other mammals, such as pet cats, dogs, pigs, rabbits, and guinea pigs. These bioengineered materials can also be used in other biological tissue remodeling scenarios. For example, they can be used for skin filling and plastic surgery, such as blepharoplasty or eyelid reconstruction, providing temporary or permanent support structures. It is understood that the above examples are only a few of the many uses, and other uses are also within the scope of this specification.

[0065] Figure 1 A schematic diagram illustrating an application scenario of a bioengineered material provided according to embodiments of this specification is shown. For example... Figure 1As shown, the bioengineered material provided in this specification can be used for corneal reshaping. The corneal filling method is as follows: a target cavity is created inside the cornea. The target cavity can accommodate a third-party material, such as an injectable bioengineered material. A pre-designed incision is made in the target cavity. The injectable liquid bioengineered material is injected into the target cavity through the pre-designed incision in the cornea. Light irradiation is applied to the bioengineered material within the target cavity, causing it to solidify, thereby transforming the bioengineered material from an injectable liquid to a solid state, increasing the thickness of the cornea, improving its mechanical strength, and completing the corneal reshaping process.

[0066] Firstly, this specification provides a bioengineered material. As described above, the bioengineered material can be used to reshape biological tissues. Specifically, the bioengineered material can be injected into biological tissues. Before injection, the bioengineered material is in a liquid state, which makes it injectable. After injection into the biological tissue, the bioengineered material located inside the biological tissue can solidify into a transparent, solid bioengineered material under light exposure. The solidified bioengineered material can perfectly conform to the shape of the biological tissue, and the solidified bioengineered material has a certain thickness and mechanical strength, thereby helping abnormal biological tissues restore their normal morphology and completing the reshaping of biological tissues.

[0067] In some embodiments, bioengineered materials can be used as drug-loaded materials to provide targeted treatment to the cornea by filling the corneal tissue. Specifically, bioengineered materials can be embedded or incorporated with specific drugs (such as anti-inflammatory drugs, growth factors, etc.) to achieve a therapeutic effect by gradually releasing the drug while increasing corneal thickness. For example, in corneal transplantation or injury repair, the use of such drug-loaded bioengineered materials can not only effectively increase corneal thickness and strength but also continuously release anti-inflammatory components and other drugs that promote tissue regeneration, thereby accelerating the healing process, reducing inflammatory responses, and minimizing side effects. This approach not only improves the precision and effectiveness of treatment but also provides patients with safer and more efficient treatment options.

[0068] When bioengineered materials are used for corneal reshaping, they can withstand the pressure of the aqueous humor after curing. Specifically, the cured bioengineered materials possess strong mechanical strength, enabling them to withstand the pressure of the aqueous humor. Aqueous humor is a transparent fluid produced by the ciliary body and fills the anterior and posterior chambers of the eye. It maintains the stability and optical properties of the eye structure by maintaining an intraocular pressure of 1.33-2.80 kPa. When bioengineered materials are injected and infiltrated into the corneal stroma, after curing, they effectively disperse and resist the pressure exerted by the aqueous humor without interfering with normal physiological functions, preventing further corneal deformation or bulging. In this way, the bioengineered materials enhance the thickness and mechanical strength of the cornea, helping to restore its normal curvature and optical properties, thereby improving the patient's vision and eye health.

[0069] Bioengineered materials not only possess excellent mechanical properties but also exhibit superior optical characteristics. Specifically, these materials have a transmittance of greater than 80% at a light wavelength of 550 nm. Furthermore, the transmittance at 550 nm can be 80%, 85%, 90%, 95%, or 100%, or any range between these values. In keratoconus treatment, high transmittance means that bioengineered materials allow most visible light to pass through, reducing light scattering and absorption, thus ensuring visual clarity and comfort for the patient.

[0070] The cell viability of bioengineered materials is greater than 80%. Specifically, a cell viability greater than 80% ensures that the bioengineered materials will not produce significant toxicity or adverse effects on cells, thus guaranteeing their effectiveness and safety in applications such as tissue engineering and drug delivery. Furthermore, the cell viability of bioengineered materials can be 80%, 85%, 90%, 95%, or 100%.

[0071] Bioengineered materials consist of a target aqueous solution and a photoinitiator solution. After solidification, the bioengineered material forms a stable three-dimensional network structure. The target aqueous solution constitutes the main framework of the bioengineered material, providing the foundation for the three-dimensional network structure. The photoinitiator solution generates free radicals and cations under specific wavelengths of light, thereby initiating cross-linking and solidification within the target aqueous solution. The interaction between the target aqueous solution and the photoinitiator solution constructs a stable three-dimensional network. This stable three-dimensional network not only enhances the mechanical strength and stability of the bioengineered material but also controls its swelling and degradation rate, enabling the bioengineered material to maintain its desired shape and function under specific conditions.

[0072] The viscosity of the target aqueous solution is thermosensitive within the target temperature range, meaning that the viscosity of the target aqueous solution changes with temperature within this range. Although the viscosity of the target aqueous solution changes with temperature within the target temperature range, the bioengineering material remains in a solid state within a specific temperature range. In other words, the bioengineering material can maintain its structural stability and physical morphology at this temperature.

[0073] For example, in orthokeratology, the sol-gel transition temperature of the target aqueous solution is between 25°C and 40°C, meaning the temperature at which the target aqueous solution changes from a liquid sol state to a solid or semi-solid gel state is between 25°C and 40°C. For some polymers, such as gelatin, the target aqueous solution is solid below 25°C. Between 25°C and 40°C, at least a portion of the target aqueous solution is in a solid or semi-solid state. Above 40°C, the target aqueous solution is liquid. For other polymers, the sol-gel transition temperature is the opposite of gelatin; for example, poly(N-isopropylacrylamide), the target aqueous solution is liquid below 30°C. Between 30°C and 35°C, at least a portion of the target aqueous solution is in a solid or semi-solid state. Above 35°C, the target aqueous solution is solid. It should be noted that the viscosity range of semi-solids is typically between 1 and 1,000 Pa·s. Substances within this range exhibit limited fluidity and solid-like properties.

[0074] Furthermore, at the first temperature, the target aqueous solution and the photoinitiator solution are mixed to form a mixed solution. At this temperature, the mixed solution is liquid and injectable. When the mixed solution is injected into the corneal stroma, the temperature within the corneal stroma is the second temperature. The second temperature is close to the sol-gel transition temperature. At this point, the mixed solution within the corneal stroma is in a semi-solid state and is not easily leaked out from the micro-incision communicating with the cavity after injection into the cornea. It is understood that the first and second temperatures correspond to the state of the mixed solution, and the sol-gel transition temperatures of different mixed solutions are not exactly the same. Therefore, the first temperature is not necessarily higher or lower than the second temperature, and needs to be determined based on the specific properties of the mixed solution.

[0075] The target aqueous solution includes the target polymer material dissolved in an aqueous solvent. The target polymer material, as the main component of the target aqueous solution, possesses characteristics such as high transparency, mechanical strength, and biocompatibility. The target polymer material includes thermosensitive and non-thermosensitive materials. In some embodiments, the target polymer material is a non-thermosensitive material. A non-thermosensitive material is a material whose physical or chemical properties do not change significantly with temperature changes. In this specification, the non-thermosensitive characteristic of the non-thermosensitive material is reflected in the fact that the target polymer material does not undergo a phase transition before and after injection into the corneal stroma in solution form. The target polymer material exhibits shear-thinning properties; its lower viscosity under high shear rate conditions is beneficial for injection; and its higher viscosity under low shear rate or no shear force conditions is beneficial for retention in tissue cavities.

[0076] Non-thermosensitive materials include at least one of hyaluronic acid, hyaluronic acid derivatives, silk fibroin, silk fibroin derivatives, collagen, collagen derivatives, alginic acid, alginic acid derivatives, dextran, dextran derivatives, polyethylene glycol, polyethylene glycol derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polylactic acid, polylactic acid derivatives, polyamino acids, polyamino acid derivatives, polypeptides, or polypeptide derivatives.

[0077] In some embodiments, the non-thermosensitive material may include only one of the following: hyaluronic acid, hyaluronic acid derivatives, silk fibroin, silk fibroin derivatives, collagen, collagen derivatives, alginate, alginate derivatives, dextran, dextran derivatives, polyethylene glycol, polyethylene glycol derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polylactic acid, polylactic acid derivatives, polyamino acids, polyamino acid derivatives, polypeptides, or polypeptide derivatives. The non-thermosensitive material may also include any combination of hyaluronic acid, hyaluronic acid derivatives, silk fibroin, silk fibroin derivatives, collagen, collagen derivatives, alginate, alginate derivatives, dextran, dextran derivatives, polyethylene glycol, polyethylene glycol derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polylactic acid, polylactic acid derivatives, polyamino acids, polyamino acid derivatives, polypeptides, or polypeptide derivatives.

[0078] In some embodiments, the target polymer material is a thermosensitive material. A thermosensitive material is a material whose physical or chemical properties change significantly with temperature variations. In this specification, the thermosensitive characteristic of the thermosensitive material is manifested in the following: when at the polymer material's first temperature, the target polymer material is in a liquid or partially liquid state, thus exhibiting flowability. At this time, the preset temperature is higher or lower than the temperature of the biological tissue. When the target polymer material is injected into biological tissue (such as the cornea), the target polymer material undergoes a phase transition with temperature changes, changing from a liquid state to a solid or semi-solid state, thereby fixing itself at the injection site and preventing easy movement. This property reduces or avoids the movement or loss of the target polymer material, ensuring the accuracy and stability of the injection process. Furthermore, the target polymer material also exhibits shear thinning properties in its solution state. Polymer shear thinning refers to the property of a polymer material where its apparent viscosity decreases with increasing shear rate when subjected to shear force. The viscosity of the target polymer material decreases with increasing shear rate; under high shear rate conditions during injection, the viscosity can be further reduced, which is beneficial for reducing injection pressure during the injection operation.

[0079] Thermosensitive materials include at least one of gelatin, gelatin derivatives, chitosan, chitosan derivatives, agar, agar derivatives, poly(N-isopropylacrylamide), poly(N-vinylcaprolactam), poly(N-vinylcaprolactam) derivatives, poly(N-vinylcaprolactam) triblock copolymers, or poly(D,L-lactic acid)-poly(ethylene glycol)-poly(D,L-lactic acid) triblock copolymers.

[0080] In some embodiments, the temperature-sensitive material may include only one of gelatin, gelatin derivatives, chitosan, chitosan derivatives, agar, agar derivatives, poly(N-isopropylacrylamide), poly(N-vinylcaprolactam), poly(N-vinylcaprolactam) derivatives, poly(N-vinylcaprolactam) triblock copolymer, or poly(D,L-lactic acid)-poly(ethylene glycol)-poly(D,L-lactic acid) triblock copolymer. Thermosensitive materials may also include gelatin, gelatin derivatives, chitosan, chitosan derivatives, agar, agar derivatives, poly-N-isopropylacrylamide, poly(N-vinylcaprolactam), poly(N-vinylcaprolactam) derivatives, poly(lactic-co-glycolic acid-polyethylene glycol-polylactic-co-glycolic acid triblock copolymers or poly(D,L-lactic acid)-polyethylene glycol-poly(D,L-lactic acid) triblock copolymers, and any combination thereof.

[0081] In some embodiments, non-thermosensitive materials and thermosensitive materials can be used in combination. For example, combining non-thermosensitive and thermosensitive materials in corneal endothelial materials can leverage the advantages of both. The long-term stability and good biocompatibility of non-thermosensitive materials provide lasting support, while the shape adjustment characteristics of thermosensitive materials according to body temperature changes enable more precise filling and immediate adhesion, thus providing a more optimized solution for corneal repair.

[0082] As mentioned above, the target polymeric material can include a variety of natural polymeric materials. However, natural polymeric materials sometimes cannot fully meet the complex requirements of specific applications, such as enhanced biocompatibility, specific functionality, or higher mechanical strength. Therefore, polymeric materials can be functionalized by introducing specific chemical groups or modified compounds to enhance their properties or endow them with new functions, thereby meeting the complex requirements of specific applications.

[0083] In some embodiments, the polymeric material comprises functional groups capable of participating in photocrosslinking. The functional groups capable of participating in photocrosslinking include at least one of the following: double-bonded functional groups, alkynyl, mercapto, aldehyde, amino, or phenolic groups. The double-bonded functional groups include at least one of the following: vinyl, acryloyl, methacryl, acrylate, methacrylate, acrylamide, methacrylamide, norbornene, cinnamate, maleimide, fumarate, or vinyl ether.

[0084] Aqueous solvents can characterize solvent systems with water as the main component. The aforementioned target polymeric materials can be dissolved in aqueous solvents. Aqueous solvents may include buffer solutions. Buffer solutions can provide suitable pH and ionic environments for bioengineering materials, and provide suitable reaction conditions for polymeric materials. Buffers include at least one of the following: acetate buffer, carbonate buffer, amino acid buffer, phosphate buffer, citrate buffer, barbiturate buffer, Earl balanced salt buffer, Hanks balanced salt buffer, cell culture medium buffer, tris(hydroxymethyl)aminomethane buffer, or 4-hydroxyethylpiperazine ethanesulfonic acid buffer. Further, the buffer may include only one of the following: acetate buffer, carbonate buffer, amino acid buffer, phosphate buffer, citrate buffer, barbiturate buffer, Earl balanced salt buffer, Hanks balanced salt buffer, cell culture medium buffer, tris(hydroxymethyl)aminomethane buffer, or 4-hydroxyethylpiperazine ethanesulfonic acid buffer. Buffers may also include any combination of acetate buffer, carbonate buffer, amino acid buffer, phosphate buffer, citrate buffer, barbiturate buffer, Earl balanced salt buffer, Hanks balanced salt buffer, cell culture medium buffer, tris(hydroxymethyl)aminomethane buffer, or 4-hydroxyethylpiperazine ethanesulfonic acid buffer.

[0085] As mentioned above, photoinitiator solutions, as another key component in bioengineering materials, not only solidify liquid bioengineering materials into solid bioengineering materials with ideal mechanical strength and stability through photochemical reactions, but also play a crucial role in promoting the effective integration of bioengineering materials with corneal tissue. Specifically, photoinitiator solutions can solidify target aqueous solutions under preset light conditions to generate transparent target materials. Under the action of photoinitiator solutions, the target polymer material itself solidifies to form a network structure bioengineering material scaffold, while chemical cross-linking occurs between collagen fibers in the corneal tissue, and cross-linking also occurs between the bioengineering material scaffold and the corneal tissue. Under this multi-cross-linking mechanism, the bioengineering material not only increases the thickness of the corneal tissue but also enhances the mechanical strength of the tissue itself.

[0086] Furthermore, the photoinitiator solution includes a first photoinitiator. Under preset illumination conditions, the first photoinitiator can cause internal cross-linking of the target polymer material. Specifically, under the action of the first photoinitiator, chemical cross-linking occurs between the chemical bonds of the target polymer material, forming a network structure of bioengineering material scaffold. Specifically, the first photoinitiator generates free radicals under the action of ultraviolet and visible light, promoting the formation of covalent bonds between functional groups including but not limited to double bonds, double bonds and thiol groups, phenol groups, and carbonyl groups and amino groups, thereby achieving internal solidification of the bioengineering material.

[0087] The first photoinitiator includes at least one of ketone photoinitiators, phosphono-oxygen photoinitiators, germane photoinitiators, azo photoinitiators, carbazole photoinitiators, xanthine photoinitiators, or bis(benzylidene)cycloalkanone two-photon initiators. Among them, ketone photoinitiators include at least one of camphorquinone, 1-hydroxycyclohexylphenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylacetone-1, or 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propanone. Phosphoryl photoinitiators include at least one of monoacylphosphonoxy, diacylphosphonoxy, phenyl(2,4,6-trimethylbenzoyl)phosphonite, or bis(2,4,6-trimethylbenzoyl)phosphonite. Germanane photoinitiators include 1,6-bis[4-(trimethylgermanylcarbonyl)phenoxy]hexane. Azo photoinitiators include at least one of azobisisobutyrazoline hydrochloride, 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide], or azobisisobutyramidine hydrochloride. Carbazole photoinitiators include ethyl 1-(6-o-methylbenzoyl-N-ethylcarbazole)-1-ethylone oxime. Xanthones include eosin Y. Bis(benzylidene)cycloalkanone two-photon initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphonite.

[0088] The following describes the photocrosslinking reaction of the target polymer material promoted by the first photoinitiator:

[0089] 1) The target polymer material is obtained from modified polymer materials containing double bonds. The double-bonded functional groups include at least one of vinyl, acryloyl, methacryl, acrylate, methacrylate, acrylamide, methacrylamide, or vinyl ether groups. The polymer materials include, but are not limited to, acrylic-modified gelatin, acrylic-modified chitosan, acrylic-modified silk fibroin, acrylic-modified sodium alginate, acrylic-modified hyaluronic acid, acrylic-modified polylysine, methacrylic acid-modified gelatin, methacrylic acid-modified chitosan, methacrylic acid-modified silk fibroin, methacrylic acid-modified sodium alginate, methacrylic acid-modified hyaluronic acid, and methacrylic acid-modified polylysine. The modified target polymer material has double bonds and can be cross-linked and cured into a hydrogel under the action of a photoinitiator using ultraviolet and visible light. The reaction formula is as follows (this reaction formula only illustrates the process of double bond cross-linking; the R group does not specifically refer to a particular polymer):

[0090]

[0091] 2) The target polymer material is obtained by modifying polymer materials with compounds containing carbon-carbon double bonds, such as norbornene, cinnamate, maleimide, and fumarate groups. These polymer materials include, but are not limited to, norbornene-modified gelatin, norbornene-modified chitosan, norbornene-modified silk fibroin, norbornene-modified sodium alginate, norbornene-modified hyaluronic acid, norbornene-modified polylysine, maleimide-modified gelatin, maleimide-modified chitosan, maleimide-modified silk fibroin, maleimide-modified sodium alginate, maleimide-modified hyaluronic acid, and maleimide-modified polylysine. The modified target polymer material with double bonds and the compound with thiol groups can be cross-linked and cured into the target product under the action of a photoinitiator using ultraviolet and visible light. The reaction formula is as follows (this reaction formula only illustrates the process of cross-linking double bonds and thiol groups; R group does not specifically refer to a certain polymer):

[0092]

[0093] 3) The target polymer material is obtained from a polymer material modified with a functional group containing a double bond. Among them, the functional group containing a double bond includes at least one of vinyl, acryloyl, methacryloyl, acrylate, methacrylate, acrylamide, methacrylamide, norbornene, cinnamate, maleimide, fumarate, or vinyl ether. Polymer materials include, but are not limited to, acrylamide gelatin, acrylamide chitosan, acrylamide silk fibroin, acrylamide sodium alginate, acrylamide hyaluronic acid, acrylamide polylysine, methacrylamide gelatin, methacrylamide chitosan, methacrylamide silk fibroin, methacrylamide sodium alginate, methacrylamide hyaluronic acid, methacrylamide polylysine, norbornene-modified gelatin, norbornene-modified chitosan, norbornene-modified silk fibroin, norbornene-modified sodium alginate, norbornene-modified hyaluronic acid, norbornene-modified polylysine, maleimide-modified gelatin, maleimide-modified chitosan, maleimide-modified silk fibroin, maleimide-modified sodium alginate, maleimide-modified hyaluronic acid, and maleimide-modified polylysine. The modified target polymer material with double bonds and the compound with thiol groups can be cross-linked and cured into the target product under the action of a photoinitiator using ultraviolet and visible light. The reaction formula is as follows (this reaction formula only illustrates the process of cross-linking double bonds and thiol groups; R group does not specifically refer to a certain polymer):

[0094]

[0095] 4) The target polymer material is obtained by modifying a polymer material with phenol-derived compounds. These phenol-derived compounds include p-hydroxyphenylpropionic acid and p-hydroxyphenylethylamine. The polymer materials include, but are not limited to, p-hydroxyphenylpropionic acid-modified gelatin, p-hydroxyphenylpropionic acid-modified chitosan, p-hydroxyphenylpropionic acid-modified silk fibroin, p-hydroxyphenylpropionic acid-modified sodium alginate, p-hydroxyphenylpropionic acid-modified hyaluronic acid, p-hydroxyphenylpropionic acid-modified polylysine, p-hydroxyphenylethylamine-modified gelatin, p-hydroxyphenylethylamine-modified chitosan, p-hydroxyphenylethylamine-modified silk fibroin, p-hydroxyphenylethylamine-modified sodium alginate, p-hydroxyphenylethylamine-modified hyaluronic acid, and p-hydroxyphenylethylamine-modified polylysine. The modified polymer material with phenolic hydroxyl groups can be cross-linked and cured into the target material under the action of a photoinitiator using ultraviolet and visible light. The reaction formula is as follows (this reaction formula only illustrates the cross-linking process of the phenolic groups; the R group does not specifically refer to a particular polymer):

[0096]

[0097] When bioengineered materials come into contact with biological tissues at the target interface, under preset illumination conditions, a second photoinitiator can cause cross-linking of the target polymer material at the target interface with the biological tissue. The second photoinitiator can also cause cross-linking of biological tissues in the target region adjacent to the target interface. Specifically, the second photoinitiator is activated under ultraviolet or blue light, generating singlet oxygen. This oxygen free radical interacts with carbonyl groups and then combines with amine groups to form covalent bonds, achieving cross-linking between collagen groups. It is understood that the target polymer material can be a natural polymer material or a polymer material modified by adding functional groups; this is not limited here.

[0098] The second photoinitiator includes at least one isofluoroazine cyclic photoinitiator. The isofluoroazine cyclic photoinitiator includes at least one of riboflavin or a riboflavin derivative.

[0099] The following explains the reaction of a second photoinitiator promoting cross-linking of protein-based target polymers with biological tissues at the target interface: Protein-based target polymers such as gelatin, silk fibroin, and collagen contain amino groups. Under ultraviolet light, the photoinitiator (riboflavin) generates free radicals (singlet oxygen). These free radicals activate the carbonyl groups (including aldehyde and carboxyl groups) of corneal collagen fibers, which then react with the amino groups to form covalent bonds, resulting in chemical cross-linking. This achieves cross-linking between the target polymer and corneal tissue, as shown in the following reaction formula:

[0100]

[0101] Bioengineered materials also include at least one co-initiator. The co-initiator can work in conjunction with the first photoinitiator to achieve internal cross-linking of the target polymer material. Specifically, some photoinitiators in the first photoinitiator cannot complete an effective photocrosslinking process on their own and require the help of a co-initiator to enhance their activity or stability, thereby promoting the formation of a stable three-dimensional network structure between polymer chains. Furthermore, the co-initiator can ensure that the photoinitiator can promote the crosslinking reaction more efficiently by providing additional active species or stabilizing the generated active intermediates, ultimately improving the mechanical properties and chemical stability of the material. The co-initiator includes at least one of triethylamine, triethanolamine, N-methyldiethanolamine, arginine, or ethyl 4-dimethylaminobenzoate. Examples of the use of photoinitiators in conjunction with co-initiators are given below. Those skilled in the art should understand that the use of other photoinitiators in conjunction with co-initiators is also within the scope of this specification.

[0102] Example 1: Ketone photoinitiators (such as camphorquinone) are combined with triethylamine to achieve photocrosslinking of the target polymer material. Specifically, camphorquinone absorbs light energy and generates free radicals. Triethylamine, as a co-initiator, can rapidly capture the generated free radicals and generate new active substances through electron transfer, promoting crosslinking between polymer chains of the target polymer material.

[0103] Example 2: Phosphine oxide photoinitiators (such as bisacylphosphine oxide) are combined with N-methyldiethanolamine to achieve photocrosslinking of the target polymer material. Specifically, bisacylphosphine oxide decomposes under light to generate phosphoryl radicals. These radicals can initiate polymerization reactions. N-methyldiethanolamine, as a co-initiator, can provide additional active intermediates to enhance the crosslinking effect.

[0104] Example 3: Ketone photoinitiators (such as 1-hydroxycyclohexylphenyl ketone) are combined with triethanolamine to achieve photocrosslinking of the target polymer material. Specifically, 1-hydroxycyclohexylphenyl ketone generates active free radicals under ultraviolet light irradiation. Triethanolamine, as a co-initiator, can stabilize these free radicals and promote the crosslinking reaction.

[0105] Example 4: Azo photoinitiators (such as azobisisobutyrazoline hydrochloride) are combined with arginine to achieve photocrosslinking of the target polymer material. Specifically, the azo photoinitiator decomposes under light irradiation to generate free radicals. Arginine acts as a co-initiator, promoting the crosslinking reaction.

[0106] Example 5: Xanthones-based photoinitiators (such as eosin Y) are combined with ethyl 4-dimethylaminobenzoate to achieve photocrosslinking of the target polymer material. Specifically, xanthones-based photoinitiators absorb energy under visible light to generate singlet oxygen or other reactive substances. Ethyl 4-dimethylaminobenzoate, as a co-initiator, can further activate these reactive substances and promote crosslinking between polymer chains in the target polymer material.

[0107] In addition to the co-initiators mentioned above, one or more drugs can be added to bioengineered materials. These drugs can provide targeted treatment based on different needs and symptoms, building upon the remodeled biological tissue. For example, for patients with corneal ulcers or other corneal surface damage, drugs that promote corneal repair can be added to bioengineered materials. These drugs help accelerate the repair process and reduce the risk of complications. Drugs that promote corneal repair include, but are not limited to, recombinant bovine basic fibroblast growth factor, recombinant human epidermal growth factor, transforming growth factor β, and insulin. For example, for patients at risk of bacterial infection, antibacterial drugs can be added to bioengineered materials. These drugs prevent further deterioration of bacterial infections. Antibacterial drugs include, but are not limited to, chlortetracycline, tobramycin, erythromycin, levofloxacin, vancomycin, and lysozyme. For example, for patients at risk of fungal infection, antifungal drugs can be added to bioengineered materials. These drugs prevent further deterioration of fungal infections. Antifungal drugs include, but are not limited to, amphotericin B, natamycin, and fluconazole. Furthermore, for patients with inflammation, anti-inflammatory and analgesic drugs can be added to bioengineered materials. These medications can reduce the release of inflammatory mediators and relieve symptoms such as redness, swelling, and pain in the eyes. Anti-inflammatory and analgesic drugs include, but are not limited to, pranoprofen, diclofenac sodium, and bromfenac sodium. Understandably, other medications can be added to bioengineered materials based on the patient's specific condition; this is not limited here.

[0108] Secondly, this specification provides a method for preparing a bioengineering material. The method includes: obtaining a target aqueous solution and a photoinitiator solution as described in the first aspect above. The photoinitiator solution includes a first photoinitiator or a mixture of a first photoinitiator and a second photoinitiator. Specifically, in some embodiments, the photoinitiator includes a first photoinitiator. In some embodiments, the photoinitiator includes a mixture of a first photoinitiator and a second photoinitiator. The target aqueous solution and the photoinitiator solution are mixed in a predetermined ratio to obtain a mixed solution.

[0109] As mentioned above, in the preparation of bioengineering materials, the target aqueous solution and photoinitiator can be mixed according to a preset ratio. Further, the target aqueous solution and photoinitiator can be mixed at a mass ratio of 99:1 to 1:1. Even further, the above preset ratio can be specifically set according to different scenarios. For example, in orthokeratology scenarios, the target aqueous solution and photoinitiator can be mixed at a 1:1 ratio. This preset ratio ensures rapid and uniform mixing of the target aqueous solution and photoinitiator solution. As another example, in drug delivery scenarios, the target aqueous solution and photoinitiator are mixed at a 99:1 ratio. This preset ratio utilizes the small molecular weight and rapid diffusion characteristics of the photoinitiator to minimize the formation of bubbles in the target aqueous solution during mixing. In other scenarios, the preset ratio can be other ratios, such as mixing the target aqueous solution and photoinitiator at ratios of 8:2, 7:3, 6:4, 9:1, etc.

[0110] The target aqueous solution has a pH value between 5.4 and 9.4. Further, the target aqueous solution has a pH value between 5.4 and 6.4, 6.4 and 7.4, 7.4 and 8.4, and 8.4 and 9.4, respectively.

[0111] The target aqueous solution can be obtained by dissolving the target polymer material in a water-based solvent. The concentration (w / w) of the target polymer material is 0.1%–80%. For example, the concentration of the polymer material can be 0.1%–1%, 1%–10%, 10%–20%, 20%–30%, 30%–40%, 40%–50%, 50%–60%, 60%–70%, or 70%–80%.

[0112] As stated in the first aspect, the target polymer material can be a natural polymer material or a modified polymer material. The following are some methods for preparing modified polymer materials. It is understood that each polymer material is not limited to one modification method; the examples below are only a few of many modified materials, and other modified materials are also within the scope of this specification.

[0113] 1) Preparation method of methacrylamide hyaluronic acid: Hyaluronic acid was dissolved in a mixed solvent of N,N-dimethylformamide and water. Then, methacrylic anhydride was slowly added dropwise in an ice bath, and the reaction continued for 24 hours. The pH was adjusted to 8-9 with sodium hydroxide. After the reaction was complete, pre-cooled anhydrous ethanol was added for precipitation. The precipitate was centrifuged at 5000 rpm for 10 min in a high-speed centrifuge to obtain crude methacrylamide hyaluronic acid. Dialysis was performed at 4℃ with frequent changes of deionized water for 3 days. After dialysis, the solution was filtered through a membrane, freeze-dried, and the obtained methacrylamide hyaluronic acid sample was stored at 4℃ in the dark for later use.

[0114] 2) Preparation method of amino-methacrylamide hyaluronic acid: Dissolve amino-methacrylamide hyaluronic acid in 2-morpholine ethanesulfonic acid buffer and adjust the pH to 4.5-6. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide to activate the carboxylic acid group. Add ethylenediamine dropwise and stir continuously at room temperature for 12 hours. After the reaction is complete, dialyze to a pure aqueous solution at pH 5 for 24 hours to purify. Freeze-dry the dialyzed solution to obtain amino-methacrylamide hyaluronic acid, store at 4°C protected from light for later use.

[0115] 3) Preparation method of methacrylamide gelatin: Dissolve gelatin in deionized water at approximately 45°C. After the gelatin is fully dissolved, add methacrylic anhydride dropwise. Stir at 500 rpm for 2-3 hours, controlling the pH between 7.0 and 11.0. After the reaction, remove excess small molecules of methacrylic anhydride using a dialysis bag, and dialyze frequently with changed deionized water for 3 days. After dialysis, filter using a filter membrane, freeze-dry, and store the resulting methacrylamide gelatin sample at 4°C in the dark for later use.

[0116] 4) Preparation method of thiolated gelatin: Dissolve gelatin in pure water at 45°C. Purge the solution into a four-necked flask with nitrogen gas and mechanically stir for 5 minutes. Then remove the flask from the water bath and slowly add thioglycolic acid dropwise. Simultaneously, activate the N-hydroxysuccinimide carboxyl group with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Continue stirring for 8 hours. After the reaction, dialyze for 48 hours to remove unreacted small molecules. Freeze-dry to obtain a white, loose thiolated gelatin, and store in a sealed container for later use.

[0117] 5) Preparation method of maleic esterified polyethylene glycol: Dissolve polyethylene glycol in anhydrous tetrahydrofuran and stir at 60°C until completely dissolved. Then add p-toluenesulfonic acid and stir for 10 min to activate. Dissolve maleic anhydride in a small amount of anhydrous tetrahydrofuran and slowly add it dropwise to the polyethylene glycol solution. Maintain the temperature at 60°C under nitrogen atmosphere. The reaction time is usually 6-24 hours. After the reaction is complete, add ice-cold diethyl ether to precipitate the product, and collect it by centrifugation. Wash with saturated sodium bicarbonate solution to remove unreacted maleic anhydride and byproducts, dialyze for 48 h, and freeze-dry to obtain white solid maleic esterified polyethylene glycol.

[0118] 6) Poly(N-isopropylacrylamide-acrylic acid-tyramine): The preparation method is as follows: N-isopropylacrylamide monomer and acrylic acid monomer are dissolved in phosphate buffer, with 2,2-azobisisobutyronitrile as the initiator. Nitrogen gas is purged for 15 min to remove oxygen, and the mixture is transferred to an oil bath at 60°C with continuous stirring for 24 h. The reaction product is precipitated with diethyl ether and vacuum dried to obtain the copolymer poly(N-isopropylacrylamide-acrylic acid). Poly(N-isopropylacrylamide-acrylic acid) is dissolved in pure water, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are added and stirred to activate the copolymer for 1 h. Tyramine hydrochloride is then added, the pH is adjusted to approximately 8.5, and the reaction is continued with stirring at room temperature for 24 h. After the reaction, excess small molecules are removed using a dialysis bag, and the product is freeze-dried to obtain the flocculent product poly(N-isopropylacrylamide-acrylic acid-tyramine).

[0119] In some embodiments, the mixed solution can be obtained by dissolving the photoinitiator in a target aqueous solution. In other embodiments, the mixed solution can be obtained by mixing a photoinitiator solution and a target aqueous solution. The photoinitiator solution can be obtained by dissolving the photoinitiator in a water-based solvent.

[0120] The concentration (w / w) of the photoinitiator is 0.0001-20%. For example, the concentration of the photoinitiator can be 0.0001-1%, 1%-2%, 2%-3%, 3%-4%, 4%-5%, 5%-6%, 6%-7%, 7%-8%, 8%-9%, 9%-10%, or 10%-20%.

[0121] The photoinitiator solution includes a first photoinitiator and a second photoinitiator. The volume ratio of the first photoinitiator to the second photoinitiator is 1:99-99:1. For example, the volume ratio of the first photoinitiator to the second photoinitiator can be 1:99, 1:9, 2:8, 3:7, 4:6, 1:1, 6:4, 7:3, 8:2, 9:1, or 99:1.

[0122] The mass fraction of photoinitiator in the photoinitiator solution is 0.0001-20%. For example, the mass fraction of photoinitiator in the photoinitiator solution can be 0.0001-1%, 1%-2%, 2%-3%, 3%-4%, 4%-5%, 5%-6%, 6%-7%, 7%-8%, 8%-9%, 9%-10%, or 10%-20%.

[0123] Further, the concentration (w / w) of the first photoinitiator is 0.0001-20%. For example, the concentration of the first photoinitiator can be 0.0001-1%, 1%-2%, 2%-3%, 3%-4%, 4%-5%, 5%-6%, 6%-7%, 7%-8%, 8%-9%, 9%-10%, or 10%-20%. The concentration (w / w) of the second photoinitiator is 0.0001-20%. For example, the concentration of the second photoinitiator can be 0.0001-1%, 1%-2%, 2%-3%, 3%-4%, 4%-5%, 5%-6%, 6%-7%, 7%-8%, 8%-9%, 9%-10%, or 10%-20%.

[0124] The mixed solution also includes a co-initiator. The volume ratio of the co-initiator to the photoinitiator is 1:99-99:1. For example, the volume ratio of the co-initiator to the photoinitiator can be 1:99, 1:9, 2:8, 3:7, 4:6, 1:1, 6:4, 7:3, 8:2, 9:1, or 99:1.

[0125] During the photo-irradiation process, the wavelength range of the irradiated light is 300 nm to 900 nm. This broad wavelength range covers the near-ultraviolet (300 nm to 400 nm), visible (400 nm to 700 nm), and near-infrared (700 nm to 900 nm) regions, meeting the diverse needs of different application scenarios. Near-ultraviolet light, with its high energy, is suitable for activating specific types of photoinitiators, promoting efficient cross-linking reactions. Furthermore, near-ultraviolet light can be used to excite ketone photoinitiators, phosphonooxy photoinitiators, and azo photoinitiators. Ketone photoinitiators include camphorquinone, 1-hydroxycyclohexylphenyl ketone, and 2,2-dimethoxy-2-phenylacetophenone. Phosphonooxy photoinitiators include monoacylphosphonooxy and diacylphosphonooxy. Other photoinitiators are the same as described in the first aspect above and will not be elaborated upon here.

[0126] Visible light not only offers a low-damage option for biological tissues but also ensures sufficient penetration depth, making it particularly suitable for delicate procedures such as corneal cross-linking in ophthalmic surgery. Furthermore, visible light can be used to excite ketone photoinitiators, phosphonooxy photoinitiators, carbazole photoinitiators, and isorhodinium ring photoinitiators. Even further, ketone photoinitiators include camphorquinone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylacetone-1. Phosphonooxy photoinitiators include phenyl(2,4,6-trimethylbenzoyl)phosphonite salts and bis(2,4,6-trimethylbenzoyl)phosphonite salts. Other photoinitiators are the same as described in the first aspect above and will not be elaborated upon here.

[0127] Near-infrared light, with its superior tissue penetration, excels in deep tissue repair and treatment, promoting cross-linking reactions in deep regions without causing significant thermal effects. Furthermore, near-infrared light can be used to excite xanthannae photoinitiators and bis(benzylidene)cycloalkanone two-photon initiators. The photoinitiators are the same as those described in the first aspect above and will not be elaborated upon here.

[0128] During phototreatment, the illumination time ranges from 1 second to 120 minutes. This wide range can be flexibly adjusted according to specific application requirements. Shorter illumination times (e.g., 1 second) are typically suitable for scenarios requiring rapid response and high photosensitivity, such as activation of certain types of photoinitiators or rapid surface curing processes. Medium-duration illumination (a few seconds to a few minutes) is commonly used for general material processing and repair applications, ensuring sufficient cross-linking reactions while avoiding the side effects of overexposure. Longer illumination times (e.g., 10 minutes) are suitable for processing complex structures or thick materials requiring deep penetration and thorough curing, ensuring that internal areas also receive sufficient light to complete the required chemical reactions. By precisely controlling the illumination time, the physical properties, mechanical strength, and biocompatibility of materials can be optimized, enabling bioengineered materials to meet the needs of various application scenarios.

[0129] When the bioengineered material is used for corneal reshaping, the preparation method of the bioengineered material further includes maintaining the mixed solution at a first temperature and injecting it into a predetermined storage space in the cornea through an injection opening. The first temperature is higher than or lower than the sol-gel transition temperature. At the first temperature, the mixed solution is liquid and injectable. The temperature is then adjusted to a second temperature. The second temperature is lower than or higher than the first temperature, and falls between the sol-gel transition temperatures. At the second temperature, the mixed solution is in a semi-solid state.

[0130] A mixed solution, after undergoing a pre-defined light irradiation treatment, can yield a solid bioengineering material. Specifically, the mixed solution comprises a target polymer material and a photoinitiator. Under pre-defined light irradiation conditions, the photoinitiator absorbs light energy and generates reactive intermediates (such as free radicals or cations). These reactive intermediates induce cross-linking reactions between the polymer chains, forming a stable three-dimensional network structure. This cross-linking process solidifies the originally liquid or gel-like mixed solution into a solid material with specific physical and chemical properties.

[0131] The following are specific embodiments related to the above-described content of this disclosure. It should be clarified that the following embodiments are merely for illustrating the bioengineering materials, preparation methods, and uses disclosed above. The specific implementation methods and parameters used are only one or more of the numerous processes and methods described above. Those skilled in the art can use other parameters to prepare the bioengineering materials according to the methods described in this specification without departing from the core spirit of the disclosure. For example, the following embodiments use hyaluronic acid, polyethylene glycol, alginate, gelatin, poly(N-isopropylacrylamide), chitosan, collagen, ε-polylysine, and silk fibroin as raw materials to prepare the bioengineering materials. Those skilled in the art will fully understand that the above-described bioengineering materials, preparation methods, and uses can also be applied using other raw materials, as long as they conform to the core spirit of the disclosure in this specification. Due to space limitations, this disclosure does not specifically describe embodiments using other raw materials here.

[0132] Example 1

[0133] 1) In this embodiment, the polymer material of the hydrogel is amino-methacrylamide hyaluronic acid.

[0134] 2) In this embodiment, the photoinitiator solution contains 1.5% by mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone and 0.0001% by mass of riboflavin. In this embodiment, the photoinitiator solution is prepared using an aqueous solution containing 10% ethanol as the solvent.

[0135] 3) Preparation of aminomethacrylamide hyaluronic acid hydrogel: Aminomethacrylamide hyaluronic acid was dissolved in phosphate buffer, with a mass fraction of 20%. The volume ratio of the aminomethacrylamide hyaluronic acid solution to the photoinitiator solution was 9:1, and the mixture was thoroughly mixed to obtain a mixed solution. The mixed solution was then subjected to photocuring treatment (irradiation at a wavelength of 365 nm for 30 min) to obtain a solid hydrogel.

[0136] 4) Application scenarios: such as Figure 1 As shown, the mixed solution of this embodiment is heated to 40-45°C to ensure good fluidity and injectability. The mixed solution of this embodiment is then injected into a circular stromal capsule with a diameter of 8 mm inside the corneal stroma. Under ultraviolet light irradiation, the mixed solution in the corneal stromal capsule is photocured to form a hydrogel, thereby increasing corneal thickness and improving corneal mechanical strength, and completing corneal reshaping.

[0137] The hydrogel performance test results are as follows:

[0138] Figure 2The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is 132 kPa.

[0139] Figure 3 A test diagram of the support properties of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 3 A is a schematic diagram of a corneal cross-section. Figure 3 B shows an actual image of an isolated porcine cornea used for orthokeratology. The normal shape of the cornea is arc-shaped, but its tissue is very soft, so the central area will sink without support. However, the cornea shaped by injecting hydrogel can maintain its arc shape, indicating that the material can improve the mechanical support strength of the corneal tissue.

[0140] Figure 4 A swelling test diagram of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 4 As shown, the cured hydrogel sample material showed no significant deformation and remained transparent after being immersed in phosphate buffer for 24 hours. This indicates that the bioengineered material of this embodiment possesses stable water absorption and swelling properties, and can be used to maintain corneal thickness.

[0141] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0142] Figure 8 A viscosity histogram of the polymer mixture solution provided according to the embodiments of this specification is shown. Figure 8 As shown in Figure A, when the shear rate changes from 1 s... -1 Increase by 100 seconds -1 At this time, the viscosity of the polymer material in this embodiment decreased from about 20 Pa·s to about 4 Pa·s, indicating that the material has shear-thinning properties, and at low shear rates, the material mixture solution is in a semi-solid state.

[0143] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0144] Figure 12 A surgical procedure flowchart according to embodiments provided in this specification is shown, such as... Figure 12As shown, Step 1 involves anesthetizing and disinfecting the ocular surface of the New Zealand rabbit. Step 2 involves making a small incision using a scleral tunneling knife. Step 3 involves bluntly separating the anterior lamellar cornea using an iris restorer to form a circular stromal capsule. Step 4 involves injecting pre-mixed bioengineering material into the stromal capsule using a syringe, allowing for control over corneal thickness and shape. Step 5 involves photocuring under ultraviolet light. Long-term observation is conducted to detect any abnormalities such as corneal whitening or lesions, and corneal thickness changes are captured using an optical coherence tomography (OCT) scanner.

[0145] Figure 13 A schematic diagram of a healthy cornea provided according to an embodiment of this specification is shown. Figure 13 As shown, a healthy cornea is generally transparent with a central thickness of approximately 350 μm. A is a white light image; B is a blue light image; C is a slit-lamp image; D is a corneal topography image; and E is an OCT image.

[0146] Figure 14 A schematic diagram illustrating the thickness variation of a hydrogel sample filling a healthy cornea according to embodiments of this specification is shown. Figure 14 As shown, the hydrogel sample of this embodiment was injected into the corneal stroma of a healthy cornea. The cornea remained transparent under white light, with no neovascularization or inflammatory response observed. Under blue light, the cornea showed no fluorescein staining, indicating that reepithelialization repair had been completed. A central thickened area was visible under a slit lamp, with a central corneal thickness of approximately 500 μm. OCT images showed that after the hydrogel sample solidified, the central corneal thickness increased by approximately 150 μm.

[0147] Figure 16 A bar graph showing the thickness variation of a hydrogel sample filling a healthy cornea according to embodiments of this specification is presented. This embodiment tested three concentrations of hydrogel, such as... Figure 16 As shown, the increased thickness of the central cornea increases with the increase of the concentration of polymer material in the hydrogel sample, indicating that bioengineering materials with different concentrations of target polymer material can be selected for regulation according to different corneal thickness requirements.

[0148] Figure 17 A bar chart showing the thickness maintenance of a hydrogel sample filling a healthy cornea according to embodiments of this specification is illustrated. Figure 17 As shown, the hydrogel sample of this embodiment was selected as the test sample, and the thickness of the sample was measured over a period of time after photocuring. Quantitative analysis was performed on the corneal thickness of the test sample at 14 days, 30 days, and 60 days. The results showed that the corneal thickness did not change over time. This indicates that the bioengineered material has superior stability in terms of corneal thickness after corneal reshaping.

[0149] Example 2

[0150] 1) In this embodiment, the polymer materials of the hydrogel are methacrylamide hyaluronic acid, polyethylene glycol diacrylate and amino polyethylene glycol acrylate.

[0151] 2) In this embodiment, the photoinitiator solution contains 0.1% by mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone and 1% by mass of sodium riboflavin phosphate. In this embodiment, the photoinitiator solution uses a pure aqueous solution as the solvent.

[0152] 3) Hydrogel Preparation: In this embodiment, the target aqueous solution was prepared by dissolving methacrylamide hyaluronic acid, polyethylene glycol diacrylate, and amino polyethylene glycol acrylate in phosphate buffer, wherein the mass fraction of methacrylamide hyaluronic acid was 2%, the mass fraction of polyethylene glycol diacrylate was 70%, and the mass fraction of amino polyethylene glycol acrylate was 10%. The target aqueous solution was mixed with the photoinitiator solution at a 1:1 ratio to obtain a mixed solution. After photocuring the mixed solution (irradiation with a wavelength of 365 nm for 30 seconds), the sample was a solid hydrogel with no flowability.

[0153] 4) Application scenario: The application scenario of this embodiment is basically the same as that of embodiment 1.

[0154] The hydrogel performance test results are as follows:

[0155] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 215 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0156] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0157] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the positive control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0158] Figure 18 A schematic diagram of corneal endothelial cells after a hydrogel sample provided according to the embodiments of this specification has filled the corneal stroma is shown. Quantitative analysis of the endothelial cell area and shape was performed using an endothelial imaging instrument, and the endothelial cell density was 2690 cells / mm². 2The corneal endothelial cells after shaping are similar in state to those of normal corneal endothelial cells before shaping, indicating that the hydrogel material has no effect on the morphology of endothelial cells after being injected into healthy corneas, and that the material has excellent biocompatibility.

[0159] Example 3

[0160] 1) In this embodiment, the polymer material of the hydrogel is alginate glycidyl methacrylate.

[0161] 2) In this embodiment, the photoinitiator solution contains 1.5% by mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone. In this embodiment, the photoinitiator solution is prepared using an aqueous solution containing 10% ethanol as the solvent.

[0162] 3) Hydrogel preparation: Glycidyl alginate methacrylate was dissolved in 4-hydroxyethylpiperazine ethanesulfonic acid buffer solution, with a mass fraction of 10%. The glycidyl alginate methacrylate solution was mixed with a photoinitiator solution at a ratio of 99:1 to obtain a mixed solution. The mixed solution was then photocured (irradiated with a wavelength of 365 nm for 30 min) to obtain a hydrogel.

[0163] 4) Application scenario: The application scenario of this embodiment is basically the same as that of embodiment 1.

[0164] The hydrogel performance test results are as follows:

[0165] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 30 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0166] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0167] Figure 8 A viscosity histogram of the polymer mixture solution provided according to the embodiments of this specification is shown. Figure 8 As shown in B, when the shear rate changes from 1 s... -1 Increase by 100 seconds -1 At this time, the viscosity of the polymer material in this embodiment decreased from about 30 Pa·s to about 3 Pa·s, indicating that the material has shear-thinning properties, and at low shear rates, the material mixture solution is in a semi-solid state.

[0168] Figure 10A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0169] Example 4

[0170] 1) In this embodiment, the polymer material of the hydrogel is methacrylamide gelatin.

[0171] 2) In this embodiment, the photoinitiator solution contains 10% by mass of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate and 1% by mass of sodium riboflavin phosphate. In this embodiment, the photoinitiator solution is prepared using phosphate buffer.

[0172] 3) Preparation of methacrylamide gelatin hydrogel: Methacrylamide gelatin was dissolved in phosphate buffer, with a mass fraction of 25%. The methacrylamide gelatin solution was mixed with a photoinitiator solution at a ratio of 9:1 to obtain a temperature-sensitive mixed solution. After photocuring the mixed solution (irradiation at 405 nm wavelength for 3 min, followed by irradiation at 365 nm wavelength for 30 min), a solid hydrogel was obtained.

[0173] 4) Application scenario: The polymer material in this embodiment is temperature sensitive, and the application scenario of this embodiment is basically the same as that of Example 1.

[0174] The hydrogel performance test results are as follows:

[0175] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 33 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0176] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0177] Figure 6 A graph showing the temperature-sensitive properties of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 6 A shows an imaging diagram of the effect of temperature on a hydrogel sample provided according to an embodiment of this specification in both cross-linked and uncross-linked states. Figure 6 B illustrates a schematic diagram showing the effect of temperature on hydrogel samples provided according to embodiments of this specification in cross-linked and uncross-linked states. Figure 6As shown in Figures A and 6B, the material remains solid below 30.0°C. When the temperature rises to approximately 38.5°C, about one-third of the uncrosslinked material sample has melted. After heating for another 3 minutes, the uncrosslinked material sample has completely melted. However, the photocrosslinked bioengineering material sample (the sample on the right in the figure) retains its complete shape even after heating for 3 minutes. This indicates that the thermosensitive material used in this method exhibits fluidity at high temperatures, while its physicochemical properties are altered after photocrosslinking, and its physical morphology is unaffected by temperature, thus maintaining good stability within the corneal stroma.

[0178] Figure 9 Viscosity histograms of the mixed solutions provided according to the embodiments of this specification under different temperatures and shear rates are shown. Figure 9 As shown, at the same temperature, the viscosity of the mixed solution in this embodiment decreases with increasing shear rate, indicating that the material has shear-thinning properties, enabling low-resistance flow during injection and restoring high viscosity after injection to maintain structural stability. Furthermore, at the same shear rate, the viscosity of the target polymer mixed solution decreases with increasing temperature, allowing for further low-resistance injection at the first temperature (45°C). After injection, the mixed solution approaches body temperature (37°C), restoring high viscosity and maintaining a semi-solid state.

[0179] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0180] In this embodiment, a corneal orthokeratology mold is used to control the shape of the cornea. Figure 19 A cross-sectional view of a molding die provided according to an embodiment of this specification is shown. Figure 19 As shown, the mold mainly consists of two cylinders, one above the other. The lower, curved area contacts the corneal surface. By controlling the shape of the bioengineered material during curing, the shape of the cornea can be regulated. The five main types of shaping molds are listed here: Mold A differs from Mold B in the diameter of the base; Mold B differs from Mold C in the curvature of the base; and Molds C, D, and E differ in the shape of the base. Different types of molds can accommodate different shapes of keratoconus.

[0181] Figure 20 This embodiment demonstrates the use of Figure 19 A schematic diagram of the cornea after corneal reshaping using mold E. Figure 20As shown, one week post-surgery, the cornea remained transparent under white light, with no neovascularization or inflammatory response observed. Under blue light, the cornea showed no fluorescein staining, indicating successful re-epithelialization repair. Due to the shape manipulation of the material, the corneal stroma exhibited a convex-concave-convex structure, which was also visible in topographic mapping, showing a structure with convex edges (approximately 550 μm) and a concave center (approximately 430 μm), consistent with the structure observed by OCT. These results indicate that the bioengineered material, after being injected into the corneal stroma, possesses the ability to regulate corneal shape.

[0182] Figure 21 A schematic diagram of corneal endothelial cells after filling the corneal stroma with a hydrogel sample provided according to the embodiments of this specification is shown. Quantitative analysis of the endothelial cell area and shape was performed using an endothelial imaging instrument, and the endothelial cell density was 2780 cells / mm². The shaped corneal endothelial cells are similar in state to unshaped normal corneal endothelial cells, indicating that the hydrogel material has no effect on the morphology of endothelial cells after injection into a healthy cornea, and that the material has excellent biocompatibility.

[0183] Figure 22 A histological staining image of the cornea after being shaped with bioengineered materials according to this embodiment is shown. Figure 22 As shown, the epithelial cells at the location of the black arrow are intact and their morphology is similar to that of a healthy cornea. The hydrogel bioengineering material adheres tightly to the stroma layer, as shown in the pentagram. Simultaneously, the bioengineering material is uniformly distributed and without gaps. This is closely related to the dual cross-linking of the bioengineering material. First, under the action of the first photoinitiator, the hydrogel bioengineering material completes its first self-cross-linking; second, under the action of the second photoinitiator, the hydrogel bioengineering material undergoes a second self-cross-linking; finally, the second photoinitiator in the bioengineering material diffuses into the adjacent corneal stroma layer, where chemical cross-linking occurs between the hydrogel bioengineering material and collagen fibers, and between collagen fibers themselves, under ultraviolet light irradiation. This multiple cross-linking not only ensures a tight fit between the material and the tissue but also enhances the mechanical strength of the tissue, better resisting intraocular pressure. Endothelial cells can also be observed through tissue staining, as shown by the black triangle. The cells have intact structures, are tightly arranged, and show no signs of apoptosis, indicating that this multiple cross-linking method has no toxic effect on endothelial cells and possesses excellent biocompatibility.

[0184] Example 5

[0185] 1) In this embodiment, the polymeric materials of the hydrogel are thiolated gelatin and maleic acid esterified polyethylene glycol.

[0186] 2) In this embodiment, the photoinitiator solution contains 1% by mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone and 0.01% by mass of flavin adenine dinucleotide. In this embodiment, the photoinitiator solution is prepared using an aqueous solution containing 10% ethanol as the solvent.

[0187] 3) Preparation of aqueous hydrogel: Thiolized gelatin and maleate-modified polyethylene glycol were dissolved in 4-hydroxyethylpiperazine ethanesulfonic acid buffer solution, wherein the mass fraction of thiolated gelatin was 10% and the mass fraction of maleate-modified polyethylene glycol was 10%. The target aqueous solution was mixed with the photoinitiator solution at a ratio of 9:1 to obtain a mixed solution. The mixed solution was then photocured (irradiated with a wavelength of 365 nm for 30 min) to obtain a solid hydrogel.

[0188] 4) Application scenario: The polymer material in this embodiment is temperature sensitive, and the application scenario of this embodiment is basically the same as that of Example 1.

[0189] The hydrogel performance test results are as follows:

[0190] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 86 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0191] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0192] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0193] Figure 11 The cytotoxicity diagram of the hydrogel sample provided according to the embodiments of this specification is shown. Cells were seeded onto the material and then subjected to vitreous staining; the results are as follows. Figure 11 As shown, the matrix cells in the hydrogel sample of this case maintained a normal spindle shape, just like the positive control group, and there was no obvious cell death. This indicates that the bioengineering material has excellent biocompatibility. Furthermore, in the hydrogel of this case, the use of different photoinitiators did not have a significant toxic effect on the cells, indicating that the material and photoinitiators have excellent biocompatibility.

[0194] Example 6

[0195] 1) In this embodiment, the polymer materials of the hydrogel are poly(N-isopropylacrylamide-acrylic acid-tyramine) and polyethylene glycol diacrylate.

[0196] 2) The photoinitiator solution in this embodiment contains 2% by mass of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate and 1% by mass of sodium riboflavin phosphate. In this embodiment, the photoinitiator solution uses a pure aqueous solution as the solvent.

[0197] 3) Hydrogel preparation: 1% (w / w) of poly(N-isopropylacrylamide-acrylic acid-tyramine) and 30% (w / w) of polyethylene glycol diacrylate were dissolved in an amino acid buffer to obtain the target aqueous solution. The target aqueous solution was mixed with a photoinitiator solution at a 1:1 ratio to obtain a mixed solution. The mixed solution was then photocured (irradiated with a wavelength of 405 nm for 2 min, followed by irradiation with a wavelength of 365 nm for 120 min) to obtain a double-network solid hydrogel.

[0198] 4) Application Scenarios: The polymer material in this embodiment is temperature-sensitive. The mixed solution of this embodiment, maintained at room temperature, is injected into a circular stromal capsule with a diameter of 8 mm within the corneal stroma. Under ultraviolet light irradiation, the mixed solution in the corneal stromal capsule is photocured to form a hydrogel, thereby increasing corneal thickness and improving corneal mechanical strength, thus completing corneal reshaping.

[0199] The hydrogel performance test results are as follows:

[0200] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 34 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0201] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0202] Figure 7 A sol-gel transition diagram of a hydrogel sample provided according to an embodiment of this specification is shown. (See attached diagram.) Figure 7 As shown, the sample exists in sol form at room temperature (approximately 24°C), exhibiting extremely high fluidity and injectability. When the temperature rises to around 37°C, the sample transforms from a sol to a gel, becoming semi-solid. After photocuring, the sample becomes a solid hydrogel with no fluidity. This indicates that the hydrogel in this embodiment can also achieve the same properties as... Figure 1 As shown, the corneal stroma is injected and then photocured to reshape the cornea and restore its thickness.

[0203] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel sample exhibited higher cell activity compared to the positive control; however, there was no significant difference in cell activity compared to the negative control. These results indicate that the material and photoinitiator have no toxic effect on corneal stromal cells.

[0204] Example 7

[0205] 1) In this embodiment, the polymeric materials of the drug-loaded hydrogel are thiolized hydroxybutyl chitosan and norbornene acylated collagen.

[0206] 2) In this embodiment, the photoinitiator solution contains 0.1% sodium riboflavin sulfonate, 0.01% eosin Y, 0.01% triethanolamine (a co-initiator), and 0.0001% N-vinylpyrrolidone. In this embodiment, the photoinitiator solution uses a pure aqueous solution as the solvent.

[0207] 3) Preparation method of drug-loaded hydrogel: Thiolated hydroxybutyl chitosan and norbornene-acyled collagen were dissolved in phosphate buffer solution, wherein the mass fraction of thiolated hydroxybutyl chitosan was 0.1% and the mass fraction of norbornene-acyled collagen was 1%. Vancomycin hydrochloride was dissolved in phosphate buffer solution to prepare a 1% vancomycin hydrochloride solution. The polymer solution, photoinitiator solution, and vancomycin hydrochloride solution were mixed at a ratio of 8:1:1 to obtain a mixed solution. The mixed solution was then subjected to photocuring treatment (irradiation at 550 nm wavelength for 15 min, followed by irradiation at 365 nm wavelength for 15 min) to obtain the drug-loaded hydrogel.

[0208] 4) Application scenario: The application scenario of this embodiment is basically the same as that of embodiment 6.

[0209] The hydrogel performance test results are as follows:

[0210] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 36 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0211] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0212] Figure 10A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0213] Figure 11 The cytotoxicity diagram of the hydrogel sample provided according to the embodiments of this specification is shown. Cells were seeded onto the material and then subjected to vitreous staining; the results are as follows. Figure 11 As shown, the matrix cells in the hydrogel sample of this case maintained a normal spindle shape, just like the positive control group, and there was no obvious cell death. This indicates that the bioengineering material has excellent biocompatibility. Furthermore, in the hydrogel of this case, the use of different photoinitiators did not have a significant toxic effect on the cells, indicating that the material and photoinitiators have excellent biocompatibility.

[0214] Example 8

[0215] 1) In this embodiment, the polymeric materials of the hydrogel are thiolated hydroxybutyl chitosan and maleimide-modified polylysine.

[0216] 2) In this embodiment, the photoinitiator solution contains 0.1% sodium riboflavin sulfonate, 0.01% eosin Y, 0.01% triethanolamine, and 0.0001% N-vinylpyrrolidone. In this embodiment, the photoinitiator solution uses pure aqueous solution as the solvent.

[0217] 3) Hydrogel preparation method: First, thiolated hydroxybutyl chitosan and maleimide-modified polylysine are dissolved in phosphate buffer solution, wherein the mass fraction of thiolated hydroxybutyl chitosan is 0.5% and the mass fraction of maleimide-modified polylysine is 2.5%. The polymer solution is mixed with the photoinitiator solution at a ratio of 7:3 to obtain a mixed solution. After photocuring the mixed solution (irradiation with a wavelength of 550 nm for 20 min and irradiation with a wavelength of 365 nm for 30 min), a solid hydrogel is obtained.

[0218] 4) Application scenario: The application scenario of this embodiment is basically the same as that of embodiment 6.

[0219] The hydrogel performance test results are as follows:

[0220] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 48 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0221] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0222] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10 As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0223] Example 9

[0224] 1) The polymer materials used in this embodiment are methacrylamide silk fibroin and polyethylene glycol diacrylate.

[0225] 2) In this embodiment, the photoinitiator is lithium phenyl (2,4,6-trimethylbenzoyl) phosphate.

[0226] 3) Hydrogel preparation: First, methacrylamide silk fibroin and polyethylene glycol diacrylate were dissolved in phosphate buffer solution, with the mass fraction of methacrylamide silk fibroin being 0.5% and the mass fraction of polyethylene glycol diacrylate being 5%. The photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate was weighed and directly dissolved in the polymer mixture solution to obtain the target mixed solution, with the mass fraction of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate being 0.1%. The target mixed solution was then subjected to photocuring treatment (irradiation at a wavelength of 405 nm for 30 min) to obtain a solid hydrogel.

[0227] 4) Application scenario: The application scenario of this embodiment is basically the same as that of embodiment 1.

[0228] The hydrogel performance test results are as follows:

[0229] Figure 2 The compressive modulus of a hydrogel sample provided according to an embodiment of this specification is shown. The compressive modulus of the hydrogel sample in this embodiment is approximately 16 kPa, which meets the mechanical performance requirements for use as a corneal stromal filling material.

[0230] Figure 5 A transmittance diagram of a hydrogel sample provided according to an embodiment of this specification is shown. For example... Figure 5 As shown, the transmittance of the samples at visible light (550nm) is greater than 80%, indicating that the material has excellent optical transparency.

[0231] Figure 10 A bar chart showing cell viability of a hydrogel sample provided according to an embodiment of this specification is shown. Figure 10As shown, the hydrogel samples showed no significant difference from the control group, and both exhibited high cell activity, indicating that the material has excellent biocompatibility with corneal cells.

[0232] Figure 15 A schematic diagram illustrating the thickness variation of a hydrogel sample filling a healthy cornea according to embodiments of this specification is shown. Figure 15 As shown, when the hydrogel sample was injected into the corneal stroma of a healthy cornea, the cornea remained transparent under white light, with no neovascularization or inflammatory response observed. Under blue light, the cornea showed no fluorescein staining, indicating that reepithelialization repair had been completed. A central thickened area was visible under a slit lamp, with a central corneal thickness of approximately 620 μm. OCT images showed that after the hydrogel sample injection, the average thickness of the corneal stroma increased by approximately 270 μm.

[0233] The foregoing has described specific embodiments of this specification. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps recited in the claims may be performed in a different order than that shown in the embodiments and may still achieve the desired result. Furthermore, the processes depicted in the drawings do not necessarily require a specific or sequential order to achieve the desired result. In some embodiments, multitasking and parallel processing are possible or may be advantageous.

[0234] In summary, after reading this detailed disclosure, those skilled in the art will understand that the foregoing detailed disclosure may be presented by way of example only and may not be restrictive. Although not explicitly stated herein, those skilled in the art will understand that this specification requires various reasonable changes, improvements, and modifications to the embodiments. These changes, improvements, and modifications are intended to be made by this specification and are within the spirit and scope of the exemplary embodiments described herein.

[0235] Furthermore, certain terms in this specification have been used to describe embodiments of this specification. For example, "an embodiment," "an embodiment," and / or "some embodiments" mean that a particular feature, structure, or characteristic described in connection with that embodiment may be included in at least one embodiment of this specification. Therefore, it is to be emphasized and understood that two or more references to "an embodiment" or "an embodiment" or "alternative embodiment" in various parts of this specification do not necessarily refer to the same embodiment. Moreover, specific features, structures, or characteristics may be suitably combined in one or more embodiments of this specification.

[0236] It should be understood that in the foregoing description of the embodiments in this specification, various features are combined in a single embodiment, drawing, or description for the purpose of simplifying the description and to aid in understanding a feature. However, this does not mean that the combination of these features is necessary, and those skilled in the art may extract some features as individual embodiments when reading this specification. That is, the embodiments in this specification can also be understood as an integration of multiple sub-embodiments. It is also valid when each sub-embodiment contains fewer than all the features of a single foregoing disclosed embodiment.

[0237] Every patent, patent application, publication of a patent application, and other material, such as articles, books, specifications, publications, documents, and literature (excluding any related historical examination documents), cited in this disclosure is incorporated herein for all purposes, including, for example, in the specification and claims of this disclosure. However, in the event of any inconsistency or conflict between the descriptions, definitions, and / or terms used in the foregoing and those used in this disclosure, the descriptions, definitions, and / or terms used in this disclosure shall prevail.

[0238] Finally, it should be understood that the embodiments disclosed herein are illustrative of the principles of the embodiments described in this specification. Other modified embodiments are also within the scope of this specification. Therefore, the embodiments disclosed in this specification are merely examples and not limitations. Those skilled in the art can implement the applications described in this specification using alternative configurations based on the embodiments in this specification. Therefore, the embodiments in this specification are not limited to the embodiments precisely described in the applications.

Claims

1. A bioengineering material for reshaping the shape of biological tissues, characterized in that, include: The target aqueous solution includes the target polymer material dissolved in an aqueous solvent; as well as A photoinitiator solution is configured to solidify the target aqueous solution under preset light conditions to generate a transparent target object.

2. The material according to claim 1, characterized in that, The photoinitiator solution comprises: A first photoinitiator is configured to cause cross-linking within the target polymer material under preset illumination conditions; and The second photoinitiator is configured such that, when the bioengineered material comes into contact with the biological tissue at the target interface, under the preset illumination conditions, the second photoinitiator causes the target polymeric material to crosslink with the biological tissue at the target interface.

3. The material according to claim 2, characterized in that, The second photoinitiator also causes cross-linking of the biological tissue in the target region adjacent to the target interface.

4. The material according to claim 2, characterized in that, The first photoinitiator includes at least one of ketone photoinitiators, phosphono-oxygen photoinitiators, germane photoinitiators, azo photoinitiators, carbazole photoinitiators, xanthan photoinitiators, or bis(benzylidene)cycloalkanone two-photon initiators.

5. The material according to claim 4, characterized in that, The ketone photoinitiator includes at least one of camphorquinone, 1-hydroxycyclohexylphenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2,2-dimethoxy-2-phenylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylpropanone-1, or 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propanone; The phosphonophosphorus photoinitiator includes at least one of monoacylphosphonophosphorus, diacylphosphonophosphorus, phenyl(2,4,6-trimethylbenzoyl)phosphonite salt or bis(2,4,6-trimethylbenzoyl)phosphonite salt; The germane-based photoinitiator includes 1,6-bis[4-(trimethylgermanylcarbonyl)phenoxy]hexane; The azo photoinitiator includes at least one of azobisisobutyrazoline hydrochloride, 2,2'-azo[2-methyl-N-(2-hydroxyethyl)propionamide], or azobisisobutyramidine hydrochloride; The carbazole photoinitiator includes 1-(6-o-methylbenzoyl-N-ethylcarbazole)-1-ethyl ketone oxime ethyl ester; The zeaxanthin-type photoinitiators include eosin Y; and The bis(benzylidene)cycloalkanone two-photon initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine salts.

6. The material according to claim 2, characterized in that, It also includes at least one co-initiator configured to cooperate with the first photoinitiator to achieve internal crosslinking of the target polymer material.

7. The material according to claim 6, characterized in that, The co-initiator includes at least one of triethylamine, triethanolamine, N-methyldiethanolamine, arginine, or ethyl 4-dimethylaminobenzoate.

8. The material according to claim 2, characterized in that, The second photoinitiator includes at least an isorhodinium ring photoinitiator; and The isorhodin cyclic photoinitiator includes at least one of riboflavin or riboflavin derivatives.

9. The material according to claim 1, characterized in that, The bioengineered material has a transmittance of more than 80% at a light wavelength of 550 nm.

10. The material according to claim 1, characterized in that, The target aqueous solution is temperature-sensitive; and The bioengineered material remains in a semi-solid state within the target temperature range.

11. The material according to claim 10, characterized in that, The sol-gel transition temperature of the target aqueous solution is between 25℃ and 40℃; The target aqueous solution is mixed with the photoinitiator solution to form a mixed solution.

12. The material according to claim 11, characterized in that, The biological tissue in question is the human cornea. The mixed solution is injectable at the first temperature; At the second temperature, the mixed solution remains in a semi-solid state after being injected into the cavity within the cornea.

13. The material according to claim 1, characterized in that, The target polymeric material includes a thermosensitive material, which includes at least one of gelatin, gelatin derivatives, chitosan, chitosan derivatives, agar, agar derivatives, poly(N-isopropylacrylamide), poly(N-vinylcaprolactam), poly(N-vinylcaprolactam) derivatives, poly(N-vinylcaprolactam) triblock copolymer, or poly(D,L-lactic acid)-poly(ethylene glycol)-poly(D,L-lactic acid) triblock copolymer.

14. The material according to claim 13, characterized in that, The target polymer material contains functional groups that can participate in photocrosslinking; The functional group includes at least one of the following: a double bond functional group, an alkynyl group, a mercapto group, an aldehyde group, an amino group, or a phenolic group; The functional group containing the double bond includes at least one of vinyl, acryloyl, methacryloyl, acrylate, methacrylate, acrylamide, methacrylamido, norbornene, cinnamate, maleimide, fumarate, or vinyl ether.

15. The material according to claim 1, characterized in that, The target polymer material includes non-thermosensitive materials, which include at least one of hyaluronic acid, hyaluronic acid derivatives, silk fibroin, silk fibroin derivatives, collagen, collagen derivatives, alginic acid, alginic acid derivatives, dextran, dextran derivatives, polyethylene glycol, polyethylene glycol derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, polylactic acid, polylactic acid derivatives, polyamino acids, polyamino acid derivatives, polypeptides, or polypeptide derivatives.

16. The material according to claim 15, characterized in that, The target polymer material contains functional groups that can participate in photocrosslinking; The functional group includes at least one of the following: a double bond functional group, an alkynyl group, a mercapto group, an aldehyde group, an amino group, or a phenolic group; The functional group containing the double bond includes at least one of vinyl, acryloyl, methacryloyl, acrylate, methacrylate, acrylamide, methacrylamido, norbornene, cinnamate, maleimide, fumarate, or vinyl ether.

17. The material according to claim 1, characterized in that, The water-based solvent further includes a buffer solution, which includes at least one of the following: acetate buffer, carbonate buffer, amino acid buffer, phosphate buffer, citrate buffer, barbiturate buffer, Earl balanced salt buffer, Hanks balanced salt buffer, cell culture medium buffer, tris(hydroxymethyl)aminomethane buffer, or 4-hydroxyethylpiperazine ethanesulfonic acid buffer.

18. A method for preparing a bioengineering material, characterized in that, include: To obtain the target aqueous solution and photoinitiator solution as described in any one of claims 1-17, wherein the photoinitiator solution comprises: a first photoinitiator or a mixture of a first photoinitiator and a second photoinitiator; as well as The target aqueous solution and the photoinitiator solution are mixed at a preset mass ratio to obtain a mixed solution.

19. The preparation method according to claim 18, characterized in that, When the bioengineered material is used for corneal reshaping, it further includes: The mixed solution is maintained at a first temperature and injected into a predetermined storage space in the cornea through the injection opening of the cornea; and Then adjust the temperature to the second temperature. The mixed solution remains in a solution state at the first temperature and is injectable; the mixed solution remains in a semi-solid state at the second temperature.

20. The preparation method according to claim 18, characterized in that, The mixed solution is subjected to a pre-defined light treatment to obtain a solid bioengineering material.

21. The preparation method according to claim 20, characterized in that, In the preset illumination process, the wavelength range of the irradiated light is 300nm to 900nm.

22. The preparation method according to claim 20, characterized in that, During the light treatment process, the light exposure time ranges from 1 second to 120 minutes.

23. The preparation method according to claim 18, characterized in that, The target aqueous solution and the photoinitiator solution are mixed at a volume ratio of 99:1 to 1:1, wherein the target aqueous solution comprises the target polymer material dissolved in a water-based solvent; The target polymer material in the target aqueous solution has a mass fraction of 0.1%-80%; The photoinitiator mass fraction in the photoinitiator solution is 0.0001%-20%.

24. The use of a bioengineering material, characterized in that, The bioengineered material as described in any one of claims 1-17 is used to fill the interior of the corneal tissue, thereby increasing the thickness of the cornea.

25. The use according to claim 24, characterized in that, The bioengineered material is used as a drug delivery system to provide targeted treatment to the cornea by filling the corneal tissue.

26. A method for reshaping the cornea, characterized in that, include: Create the target cavity inside the cornea; The bioengineering material as described in any one of claims 1-17 is injected into the target cavity through a pre-designed incision on the cornea; as well as The bioengineered material inside the target cavity is irradiated with light, causing the bioengineered material to solidify, thereby increasing the thickness of the cornea.